Artefact formation during acid hydrolysis of saponins from Medicago spp. (June 2017) - Tava, Aldo; Biazzi, Elisa; Mella, Mariella; Quadrelli, Paolo; Avato, Pinarosa
Abstract: Artefact compounds obtained during acid hydrolysis of saponins from Medicago spp. (Fabaceae), have been monitored and evaluated by GC-FID. Their identification has been performed by GC-MS and 1 H and 13 C NMR. Saponins with different substituents on the triterpenic pentacyclic aglycones were considered, and their hydrolysis products were detected and quantified during 10 h of time course reaction. From soyasapogenol B glycoside the well known soyasapogenols B, C, D and F were obtained together with a previously undescribed sapogenol artefact identified as 3 β, 22 β, 24-trihydroxyolean-18(19)-en and named soyasapogenol H. From a zanhic acid saponin two major artefact compounds identified as 2 β, 3 β, 16 α -trihydroxyolean-13(18)-en-23, 28-dioic acid and 2 β, 3 β, 16 α -trihydroxyolean-28, 13 β -olide-23-oic acid were obtained, together with some zanhic acid. Other compounds, detected in very small amount in the reaction mixture, were also tentatively identified based on their GC-MS and UV spectra. The other most characteristic saponins in Medicago spp., hederagenin, bayogenin and medicagenic acid glycosides, under acidic condition of hydrolysis, released instead the correspondent aglycones and generated a negligible amount of artefacts. Nature of artefacts and mechanism of their formation, involving a stable tertiary carbocation, is here proposed and discussed for the first time. Graphical abstract: Saponins from Medicago spp. with different substituents on the aglycone moieties were subjected to acid hydrolysis and several sapogenol artefacts were identified. A transposition of the double bond on the triterpenic structure and the formation of the corresponding -olide derivatives have been described. Highlights: Artefacts from acid hydrolysis of pure saponins from Medicago spp. have been evaluated. Saponins with different substituents on the triterpenic aglycones were considered. From soyasapogenol B saponin known artefacts and one unreported compound were detected. From a zanhic acid saponin two major artefacts were identified, together with some zanhic acid. The mechanism of their formation is here proposed and discussed.